Motivasi Petani Mempertahankan Lahan Pertanian di Wilayah Pinggiran Kota Malang (Studi Kasus Kawasan Perkotaan Karangploso Kabupaten Malang) - Baiq Rindang Aprildahani; Abdul Wahid Hasyim; Turniningtyas Ayu Rachmawati (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2017)
The needs for space to support urban activities causes the expansion of urban regions in Malang. Urban activities started moving spread from the city center to suburban areas (urban sprawl). Kawasan Perkotaan Karangploso (KPK), Kabupaten Malang is one of the suburban areas. Urban sprawl is conversion of agricultural land in the suburbs. Find out about the character of farmers and set up positive mental are step that must be taken to preserve agricultural land. This study determines the influence of agricultural social, environmental, economic and policy on the farmer motivation to preserve agricultural land. The research uses statistical methods which is structural equation modeling (SEM) type of partial least square (PLS). Based on the analysis of PLS, the policy and social variables influence the farmer motivation to preserve agricultural land in KPK. Farmers motivation to preserve agricultural land will be high if policy and social variables in good condition. If the goal is increasing the farmer motivation to preserve agricultural land, the improvement of policy and social variables should be heed and priority, especially if there is constraint in terms of cost or time. Meanwhile, the economic and environmental variables can be calculates thereafte